Assessment of the readability of patient-facing materials for the most commonly prescribed medicines in Ireland - Mohamed Elhassadi; Patrick Moynagh; Anne Sinead Doherty; Claire Gorry; Caroline McCarthy (Health Literacy and Communication Open)
Background Patient-facing medicine information materials are essential to support the safe use of medicines, empowering patients to make informed decisions about their health. This study aimed to evaluate the readability of patient information materials on medicines for the top 100 most commonly dispensed medicines in Ireland.Methods This cross-sectional study was conducted in September 2024. The readability of patient information leaflets, decision aids and online information from the health service in both Ireland and the UK was assessed using the Sydney Health Literacy (SHeLL) Editor, which utilizes the Simple Measure of Gobbledygook (SMOG) index to estimate the number of years of education required to understand a piece of writing.Results Overall, 265 different information sources on 88 medicines were identified and included in this analysis. The average readability score was 10.28 (SD 1.24), exceeding the optimal target of below eight, which corresponds to an 8th-grade reading level. While all materials exceeded the optimal target score, patient decision aids consistently demonstrated better readability compared to PILs and other online health resources.Discussion These findings highlight the need for improved patient information tools to enhance patient understanding, particularly among those with limited health literacy. This study advocates for further research and targeted interventions to simplify written medicines information to address existing communication gaps and ensure equitable access to healthcare information.